Approaches to Reducing Risk of COVID-19 Infections in Prisons and Immigration Detention Centers: A Commentary - Kelly, Kate (Criminal justice review, 2024)
Although often left out of public health efforts and policy decisions, prisons, jails, and detention centers are integral to community health. With an average of 650,000 citizens returning home from prison each year in the United States, and thousands of correctional staff members returning home every night, there are millions of touchpoints between outside communities and carceral settings. For this reason, carceral communities should be central to planning and policy making in response to the spread of the COVID-19 illness. As social workers and clinicians, we are urgently concerned that efforts to prevent COVID-19 infections in prisons are underdeveloped and inadequate in the face of a fast-spreading virus. In this commentary, we outline a set of public health, policy, and clinical recommendations based upon the existing literature to mitigate various risks to the well-being of carceral communities.